SPE Western Regional Meeting 2018
DOI: 10.2118/190061-ms
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of CO2-Foam Injection through Resistivity and Pressure Measurements

Abstract: This paper focuses on the use of combined resistivity and pressure measurements to determine the effectiveness of foam as a mobility control method and presents a theoretical framework to describe the expected resistivity changes during CO2-Foam displacements. With this objective, we first provide equations to estimate the resistivity for CO2-Foam systems and then utilize Population Based (PBE) and Steady-State Foam models to quantify these effects. Using analytical solutions based on the fractional flow theor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…Other foam parameters were also selectively adjusted, and results showed they had less of an impact on the overall pressure match. However, considering the non-unique nature of parameter estimation [28], the effects of these foam parameters should be addressed by more direct indicators of foam saturation, such as resistivity measurements [16].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Other foam parameters were also selectively adjusted, and results showed they had less of an impact on the overall pressure match. However, considering the non-unique nature of parameter estimation [28], the effects of these foam parameters should be addressed by more direct indicators of foam saturation, such as resistivity measurements [16].…”
Section: Resultsmentioning
confidence: 99%
“…Based on previous comparable studies with CO 2 injections [16], it has been suggested that crosswell pressure testing, in addition to seismic and electromagnetic data, could be deployed for CO 2 foam monitoring. In crosswell pressure testing, a series of pressure pulses is induced by shutting down the injector, and the pressure measurements are taken at the observation well.…”
Section: Pressure Testing For Foam Monitoringmentioning
confidence: 99%